Graft-modified PBAT / CNC material, preparation method thereof and application of graft-modified PBAT / CNC material in polyester packaging material
By aminating the modified cellulose nanocrystals and grafting them onto the PBAT molecular chain, the shortcomings of PBAT materials in terms of mechanical properties, antibacterial properties and barrier properties are solved, and the comprehensive performance of polyester packaging materials is significantly improved, which is suitable for a wide range of applications in the packaging industry.
Patent Information
- Application Number
- CN202510181393.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional PBAT materials have shortcomings in mechanical properties, antibacterial properties and barrier properties, which are difficult to meet packaging needs. The compatibility and interface binding force of cellulose nanocrystals and PBAT matrix are insufficient, which affects the performance of composite materials.
By aminating the modified cellulose nanocrystals and grafting them onto the PBAT molecular chain, the compatibility and interface binding force between CNC and PBAT matrix are significantly improved. Combined with a specific ratio of esterification/polycondensation process and a tetraisopropyl titanate catalytic system, graft modified PBAT/CNC materials with excellent mechanical properties are prepared.
It significantly improves the mechanical properties, antibacterial activity and barrier properties of polyester packaging materials, while maintaining biodegradable properties, providing strong support for the widespread application of PBAT in the packaging industry.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polyester materials, and in particular relates to a graft-modified PBAT / CNC material and a preparation method thereof and application thereof in polyester packaging materials. Background Art
[0002] With the increasing awareness of environmental protection, the application of biodegradable polyester materials in the packaging field has received increasing attention. PBAT (polybutylene adipate / terephthalate), as a polyester material with good ductility and biodegradability, has been widely used in the field of packaging materials in recent years. However, traditional PBAT materials have deficiencies in mechanical properties, antibacterial properties, and barrier properties, which make it difficult to meet packaging needs and urgently need further improvement.
[0003] Cellulose nanocrystals (CNC) are nanomaterials with high specific surface area and excellent mechanical properties, and their introduction can effectively enhance the performance of PBAT materials. However, due to the poor compatibility of the hydroxyl groups on the surface of CNC with the hydrophobic PBAT matrix, agglomeration is prone to occur, resulting in insufficient interfacial bonding of the composite material, and direct blending is difficult to fully utilize the advantages of CNC.
[0004] At present, although there are some studies on the modification of PBAT materials, the method for preparing high-performance polyester packaging materials by grafting modified PBAT / CNC materials is still imperfect. Therefore, developing a simple and efficient method for preparing grafted modified PBAT / CNC materials and applying it to polyester packaging materials is of great significance for improving the comprehensive performance of biodegradable materials and broadening their application fields. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a grafted modified PBAT / CNC material. By aminated modified cellulose nanocrystals, the aminated cellulose nanocrystals are successfully grafted onto the PBAT molecular chain, which significantly improves the compatibility and interfacial bonding strength between CNC and the PBAT matrix. The obtained grafted modified PBAT / CNC is applied to polyester packaging materials to improve the mechanical properties of the packaging materials.
[0006] Another object of the present invention is to provide a graft-modified PBAT / CNC material and its application in polyester packaging materials.
[0007] The technical solution adopted by the present invention is as follows: The preparation method of the graft-modified PBAT / CNC material comprises the following steps: (1) adding cellulose nanocrystals to anhydrous ethanol, and then adding 3-aminopropyltriethoxysilane to carry out magnetic stirring reaction after ultrasonic dispersion. After the reaction, the reaction is centrifuged, washed, and dried to obtain amino cellulose nanocrystals; (2) 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride are added to a reactor, and then amino cellulose nanocrystals are added. Under nitrogen protection, the temperature is raised to carry out an esterification reaction. After the esterification reaction is completed, tetraisopropyl titanate is added, and the temperature is continued to be raised to carry out a polycondensation reaction. After the polycondensation reaction is completed, the product is dissolved in chloroform and filtered to obtain a grafted modified PBAT / CNC material; wherein the amount of amino cellulose nanocrystals added is 1-2wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
[0008] In the step (1), the mass volume ratio of cellulose nanocrystals to anhydrous ethanol is (5-10) mg:100 mL.
[0009] In the step (1), the mass ratio of the added amount of 3-aminopropyltriethoxysilane to the cellulose nanocrystals is (0.5-0.7):1.
[0010] In the step (1), the ultrasonic dispersion time is 30-40 minutes; the magnetic stirring reaction temperature is 70-80°C and the reaction time is 6-8 hours.
[0011] In the step (2), the molar ratio of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride is (1.2-1.8):1:(0.8-1.2):(0.05-0.08).
[0012] In the step (2), the amount of tetraisopropyl titanate added is 0.08-0.1 wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
[0013] In the step (2), the temperature of the esterification reaction is 200-210°C; the temperature of the polycondensation reaction is 230-240°C.
[0014] The graft-modified PBAT / CNC material is prepared by the above-mentioned method for preparing the graft-modified PBAT / CNC material.
[0015] The graft-modified PBAT / CNC material is used to prepare polyester packaging materials.
[0016] The polyester packaging material comprises the following raw materials in parts by weight: Graft modified PBAT / CNC material: 80-85 parts; Antibacterial modified montmorillonite: 3-4 parts; Nano zinc oxide: 2-3 parts; Graphene nanosheets: 1-2 parts; Epoxidized soybean oil: 3-5 parts; Chain extender ADR-4370S: 0.3-0.5 parts; Antioxidant 1010: 0.1-0.3 parts; Di-tert-butylperoxyisopropylbenzene: 0.05-0.08 parts.
[0017] The method for preparing the antibacterial modified montmorillonite comprises the following steps: 1) dissolving chitosan in deionized water, adjusting the pH value of the system to 6-7 with acetic acid, then adding quaternary ammonium salt, stirring and reacting at 70-80° C. for 6-8 hours, washing with anhydrous ethanol after the stirring reaction, and obtaining chitosan quaternary ammonium salt after washing; wherein the quaternary ammonium salt is composed of octadecyltrimethylammonium chloride and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:(1-3); and the molar ratio of chitosan to quaternary ammonium salt is 1:(1-3); 2) dispersing sodium montmorillonite in deionized water to form a suspension, then adding the chitosan quaternary ammonium salt and zinc stearate obtained in step 1), stirring and reacting again at 70-80° C. for 6-8 hours, filtering and drying the mixture after the reaction to obtain antibacterial modified montmorillonite; wherein the molar ratio of sodium montmorillonite to chitosan quaternary ammonium salt is 1:(0.8-1); and the amount of zinc stearate added is 0.5-1wt.% of the total amount of chitosan quaternary ammonium salt.
[0018] The chain extender ADR-4370S was purchased from BASF, Germany.
[0019] The method for preparing the polyester packaging material comprises the following steps: The raw materials of the formula components are added to a high-speed mixer and mixed evenly, and then added to a twin-screw extruder for melt blending. The melt-blended materials are extruded through a die head, cut into particles after cooling and solidification, and then the particles are blown into film to obtain PBAT-based polyester packaging materials.
[0020] The temperature of the melt blending is 220-240°C.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the grafted modified PBAT / CNC material of the present invention significantly improves the interfacial compatibility and interfacial bonding force between CNC and PBAT matrix by aminated modified cellulose nanocrystals, and combines the esterification / polycondensation process with a specific ratio and the tetraisopropyl titanate catalyst system to prepare a grafted modified PBAT / CNC material with excellent mechanical properties. At the same time, the material is applied to polyester packaging materials, and further synergistically matched with antibacterial modified montmorillonite, nano zinc oxide, graphene nanosheets and other components, the resulting polyester packaging material has excellent antibacterial activity, mechanical strength and barrier properties, while maintaining biodegradable properties, providing strong support for the wide application of PBAT in the packaging industry. DETAILED DESCRIPTION
[0022] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.
[0023] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0024] Example 1 The preparation method of the graft-modified PBAT / CNC material comprises the following steps: (1) Add cellulose nanocrystals to anhydrous ethanol, the mass volume ratio of cellulose nanocrystals to anhydrous ethanol is 5 mg:100 mL; add 3-aminopropyltriethoxysilane after ultrasonic dispersion for 30 min, and react under magnetic stirring at 70°C for 8 h. After the reaction, centrifuge, wash with ethanol three times, and vacuum dry at 60°C for 12 h to obtain amino cellulose nanocrystals; wherein the mass ratio of 3-aminopropyltriethoxysilane added to cellulose nanocrystals is 0.5:1; (2) 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride in a molar ratio of 1.2:1:0.8:0.05 were added to the reactor, and then amino cellulose nanocrystals were added. Under nitrogen protection, the temperature was raised to 200°C for esterification reaction for 3 hours. After the esterification reaction was completed, tetraisopropyl titanate was added, and the temperature was continued to be raised to 230°C for polycondensation reaction for 3 hours. After the polycondensation reaction was completed, the product was dissolved in chloroform and filtered to obtain a grafted modified PBAT / CNC material; wherein the amount of amino cellulose nanocrystals added was 1wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added; and the amount of tetraisopropyl titanate added was 0.08wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
[0025] The polyester packaging material comprises the following raw materials in parts by weight: Graft modified PBAT / CNC material: 80 parts; Antibacterial modified montmorillonite: 3 parts; Nano zinc oxide: 2 parts; Graphene nanosheets: 1 part; Epoxidized soybean oil: 3 parts; Chain extender ADR-4370S: 0.3 parts; Antioxidant 1010: 0.1 part; Di-tert-butyl peroxyisopropylbenzene: 0.05 parts; The method for preparing the antibacterial modified montmorillonite comprises the following steps: 1) dissolving chitosan in deionized water, adjusting the pH value of the system to 6 with acetic acid, then adding quaternary ammonium salt, stirring and reacting at 70° C. for 8 hours, washing with anhydrous ethanol after the stirring reaction, and obtaining chitosan quaternary ammonium salt after washing; wherein the quaternary ammonium salt is composed of a mixture of octadecyltrimethylammonium chloride and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:1; and the molar ratio of chitosan to the quaternary ammonium salt is 1:1; 2) dispersing sodium montmorillonite in deionized water to form a suspension, then adding the chitosan quaternary ammonium salt and zinc stearate obtained in step 1), stirring and reacting again at 70° C. for 8 h, filtering and drying the mixture after the reaction to obtain antibacterial modified montmorillonite; wherein the molar ratio of sodium montmorillonite to chitosan quaternary ammonium salt is 1:0.8; and the amount of zinc stearate added is 0.5wt.% of the total amount of chitosan quaternary ammonium salt.
[0026] The method for preparing the PBAT-based polyester packaging material comprises the following steps: The raw materials of the formula components are added to a high-speed mixer and mixed evenly, and then added to a twin-screw extruder, and melt-blended at 230±10°C and a screw speed of 500r / min. The melt-blended material is extruded through a die head, cooled and solidified, and then cut into particles, and then the particles are blown into film to obtain a PBAT-based polyester packaging material.
[0027] Example 2 The preparation method of the graft-modified PBAT / CNC material comprises the following steps: (1) Add cellulose nanocrystals to anhydrous ethanol, the mass volume ratio of cellulose nanocrystals to anhydrous ethanol is 7 mg:100 mL; add 3-aminopropyltriethoxysilane after ultrasonic dispersion for 35 min, and react under magnetic stirring at 75 ° C for 7 h. After the reaction, centrifuge, wash with ethanol for 3 times, and vacuum dry at 60 ° C for 12 h to obtain amino cellulose nanocrystals; wherein the mass ratio of 3-aminopropyltriethoxysilane added to cellulose nanocrystals is 0.6:1; (2) 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride in a molar ratio of 1.5:1:1:0.07 were added to the reactor, and then amino cellulose nanocrystals were added. Under nitrogen protection, the temperature was raised to 205°C for esterification reaction for 3 hours. After the esterification reaction was completed, tetraisopropyl titanate was added, and the temperature was continued to be raised to 235°C for polycondensation reaction for 3 hours. After the polycondensation reaction was completed, the product was dissolved in chloroform and filtered to obtain a grafted modified PBAT / CNC material; wherein the amount of amino cellulose nanocrystals added was 1.5wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added; the amount of tetraisopropyl titanate added was 0.09wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
[0028] The polyester packaging material comprises the following raw materials in parts by weight: Graft modified PBAT / CNC material: 83 parts; Antibacterial modified montmorillonite: 3.5 parts; Nano zinc oxide: 2.5 parts; Graphene nanosheets: 1.5 parts; Epoxidized soybean oil: 4 parts; Chain extender ADR-4370S: 0.4 parts; Antioxidant 1010: 0.2 parts; Di-tert-butyl peroxyisopropylbenzene: 0.06 parts; The method for preparing the antibacterial modified montmorillonite comprises the following steps: 1) dissolving chitosan in deionized water, adjusting the pH value of the system to 7 with acetic acid, then adding quaternary ammonium salt, stirring and reacting at 75° C. for 7 hours, washing with anhydrous ethanol after the stirring reaction, and obtaining chitosan quaternary ammonium salt after washing; wherein the quaternary ammonium salt is composed of octadecyltrimethylammonium chloride and 2,3-epoxypropyltrimethylammonium chloride mixed in a molar ratio of 1:2; and the molar ratio of chitosan to quaternary ammonium salt is 1:2; 2) dispersing sodium montmorillonite in deionized water to form a suspension, then adding the chitosan quaternary ammonium salt and zinc stearate obtained in step 1), stirring and reacting again at 75° C. for 7 hours, filtering and drying the mixture after the reaction to obtain antibacterial modified montmorillonite; wherein the molar ratio of sodium montmorillonite to chitosan quaternary ammonium salt is 1:0.9; and the amount of zinc stearate added is 0.7wt.% of the total amount of chitosan quaternary ammonium salt.
[0029] The preparation method of the polyester packaging material has the same steps as Example 1.
[0030] Example 3 The preparation method of the graft-modified PBAT / CNC material comprises the following steps: (1) Add cellulose nanocrystals to anhydrous ethanol, the mass volume ratio of cellulose nanocrystals to anhydrous ethanol is 10 mg:100 mL; add 3-aminopropyltriethoxysilane after ultrasonic dispersion for 40 min, and react under magnetic stirring at 80° C. for 6 h. After the reaction, centrifuge, wash with ethanol three times, and vacuum dry at 60° C. for 12 h to obtain amino cellulose nanocrystals; wherein the mass ratio of 3-aminopropyltriethoxysilane added to cellulose nanocrystals is 0.7:1; (2) 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride in a molar ratio of 1.8:1:1.2:0.08 were added to the reactor, and then amino cellulose nanocrystals were added. Under nitrogen protection, the temperature was raised to 210°C for esterification reaction for 2.5 hours. After the esterification reaction was completed, tetraisopropyl titanate was added, and the temperature was further raised to 240°C for polycondensation reaction for 2.5 hours. After the polycondensation reaction was completed, the product was dissolved in chloroform and filtered to obtain a grafted modified PBAT / CNC material; wherein the amount of amino cellulose nanocrystals added was 2wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added; and the amount of tetraisopropyl titanate added was 0.1wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
[0031] The polyester packaging material comprises the following raw materials in parts by weight: Graft modified PBAT / CNC material: 85 parts; Antibacterial modified montmorillonite: 4 parts; Nano zinc oxide: 3 parts; Graphene nanosheets: 2 parts; Epoxidized soybean oil: 5 parts; Chain extender ADR-4370S: 0.5 parts; Antioxidant 1010: 0.3 parts; Di-tert-butyl peroxyisopropylbenzene: 0.08 parts; The method for preparing the antibacterial modified montmorillonite comprises the following steps: 1) dissolving chitosan in deionized water, adjusting the pH value of the system to 7 with acetic acid, then adding quaternary ammonium salt, stirring and reacting at 80° C. for 6 hours, washing with anhydrous ethanol after the stirring reaction, and obtaining chitosan quaternary ammonium salt after washing; wherein the quaternary ammonium salt is composed of octadecyltrimethylammonium chloride and 2,3-epoxypropyltrimethylammonium chloride mixed in a molar ratio of 1:3; and the molar ratio of chitosan to quaternary ammonium salt is 1:3; 2) dispersing sodium montmorillonite in deionized water to form a suspension, then adding the chitosan quaternary ammonium salt and zinc stearate obtained in step 1), stirring and reacting again at 80° C. for 6 hours, filtering and drying the mixture after the reaction to obtain antibacterial modified montmorillonite; wherein the molar ratio of sodium montmorillonite to chitosan quaternary ammonium salt is 1:1; and the amount of zinc stearate added is 1wt.% of the total amount of chitosan quaternary ammonium salt.
[0032] The preparation method of the polyester packaging material has the same steps as Example 1.
[0033] Comparative Example 1 The difference from Example 1 is that the graft-modified PBAT / CNC material is replaced by PBAT in equal amounts, and the rest is the same as Example 1.
[0034] Comparative Example 2 The difference from Example 1 is that the antibacterial modified montmorillonite is replaced by sodium-based montmorillonite in equal amounts, and the rest is the same as Example 1.
[0035] The polyester packaging materials prepared in Examples 1-3 and Comparative Example 1 were respectively tested for mechanical properties and barrier properties, and the test methods are as follows: Tensile strength, MPa: Tested in accordance with GB / T 1040.3-2006; Elongation at break, %: Tested in accordance with GB / T 1040.3-2006; Water vapor transmission rate, g / (m 2 24h): Tested in accordance with GB / T 1037-2021.
[0036] The test results are shown in Table 1.
[0037] Table 1 Mechanical properties and barrier properties test results
[0038] It can be seen from the test data in Table 1 that the polyester packaging materials prepared in Examples 1-3 have excellent mechanical properties, and due to the nano-filling effect of CNC and the dense barrier layer formed by uniform dispersion, the barrier properties are good.
[0039] In Comparative Example 1, since the graft-modified PBAT / CNC material was not used, the tensile strength and elongation at break of the obtained polyester packaging material were significantly lower than those in the embodiment, and the water vapor permeability was relatively high.
[0040] The polyester packaging materials prepared in Examples 1-3 and Comparative Example 2 were respectively tested for antibacterial properties, and the test method was as follows: Staphylococcus aureus inhibition rate, %: tested in accordance with GB / T 31402-2015; Escherichia coli inhibition rate, %: tested in accordance with GB / T 31402-2015.
[0041] The test results are shown in Table 2.
[0042] Table 2 Antibacterial performance test results
[0043] It can be seen from the test data in Table 2 that the antibacterial properties of the polyester packaging materials prepared in Examples 1-3 are improved due to the addition of antibacterial modified montmorillonite and the synergistic effect of chitosan quaternary ammonium salt and zinc stearate.
[0044] In Comparative Example 2, since no antibacterial modified montmorillonite was used, there was a lack of antibacterial active ingredients and the antibacterial rate was low.
Claims
1. A method for preparing a graft-modified PBAT / CNC material, characterized in that: The following steps are involved: (1) adding cellulose nanocrystals to anhydrous ethanol, and then adding 3-aminopropyltriethoxysilane to carry out magnetic stirring reaction after ultrasonic dispersion. After the reaction, the reaction is centrifuged, washed, and dried to obtain amino cellulose nanocrystals; (2) 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride are added to a reactor, and then amino cellulose nanocrystals are added. Under nitrogen protection, the temperature is raised to carry out an esterification reaction. After the esterification reaction is completed, tetraisopropyl titanate is added, and the temperature is continued to be raised to carry out a polycondensation reaction. After the polycondensation reaction is completed, the product is dissolved in chloroform and filtered to obtain a grafted modified PBAT / CNC material; wherein the amount of amino cellulose nanocrystals added is 1-2wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
2. The method for preparing the graft-modified PBAT / CNC material according to claim 1, characterized in that: In the step (1), the mass volume ratio of cellulose nanocrystals to anhydrous ethanol is (5-10) mg:100 mL; the mass ratio of the added amount of 3-aminopropyltriethoxysilane to the cellulose nanocrystals is (0.5-0.7) :
1.
3. The method for preparing the graft-modified PBAT / CNC material according to claim 1, characterized in that: In the step (1), the ultrasonic dispersion time is 30-40 minutes; the magnetic stirring reaction temperature is 70-80°C and the reaction time is 6-8 hours.
4. The method for preparing the graft-modified PBAT / CNC material according to claim 1, characterized in that: In the step (2), the molar ratio of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride is (1.2-1.8):1:(0.8-1.2):(0.05-0.08).
5. The method for preparing the graft-modified PBAT / CNC material according to claim 1, characterized in that: In the step (2), the amount of tetraisopropyl titanate added is 0.08-0.1 wt.% of the total amount of 1,4-butanediol, terephthalic acid, adipic acid and maleic anhydride added.
6. The method for preparing the graft-modified PBAT / CNC material according to claim 1, characterized in that: In the step (2), the temperature of the esterification reaction is 200-210°C; the temperature of the polycondensation reaction is 230-240°C.
7. A graft-modified PBAT / CNC material, characterized in that: The graft-modified PBAT / CNC material is prepared by the preparation method of any one of claims 1 to 6.
8. An application of the graft-modified PBAT / CNC material according to claim 7, characterized in that: Used to prepare polyester packaging materials.
9. The use of the graft-modified PBAT / CNC material according to claim 8, characterized in that: The polyester packaging material comprises the following raw materials in parts by weight: Graft modified PBAT / CNC material: 80-85 parts; Antibacterial modified montmorillonite: 3-4 parts; Nano zinc oxide: 2-3 parts; Graphene nanosheets: 1-2 parts; Epoxidized soybean oil: 3-5 parts; Chain extender ADR-4370S: 0.3-0.5 parts; Antioxidant 1010: 0.1-0.3 parts; Di-tert-butylperoxyisopropylbenzene: 0.05-0.08 parts.
10. The use of the graft-modified PBAT / CNC material according to claim 9, characterized in that: The method for preparing the antibacterial modified montmorillonite comprises the following steps: 1) dissolving chitosan in deionized water, adjusting the pH value of the system to 6-7, then adding quaternary ammonium salt, stirring and reacting at 70-80° C. for 6-8 hours, washing with anhydrous ethanol after the stirring reaction, and obtaining chitosan quaternary ammonium salt after washing; wherein the quaternary ammonium salt is composed of octadecyltrimethylammonium chloride and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:(1-3); and the molar ratio of chitosan to quaternary ammonium salt is 1:(1-3); 2) dispersing sodium montmorillonite in deionized water to form a suspension, then adding the chitosan quaternary ammonium salt and zinc stearate obtained in step 1), stirring and reacting again at 70-80° C. for 6-8 hours, filtering and drying the mixture after the reaction to obtain antibacterial modified montmorillonite; wherein the molar ratio of sodium montmorillonite to chitosan quaternary ammonium salt is 1:(0.8-1); and the amount of zinc stearate added is 0.5-1wt.% of the total amount of chitosan quaternary ammonium salt.
Citation Information
Patent Citations
Biodegradable polyester resin composition, nonwoven fabric, film, and method for preparing biodegradable polyester resin composition
CN113736069A
Low-acid-value long-acting antibacterial degradable polyester as well as preparation method and application thereof
CN116854898A
Chitosan quaternary ammonium salt / organic montmorillonite nano composite material and preparation method thereof
CN1927924A
KR20240080032A